Epidemiology and Etiology of Young Stroke. (18th July 2011) - Griffiths, Dayna; Sturm, Jonathan
Abstract : Introduction . Stroke in people under 45 years of age is less frequent than in older populations but has a major impact on the individual and society. In this article we provide an overview of the epidemiology and etiology of young stroke. Methods . This paper is based on a review of population-based studies on stroke incidence that have included subgroup analyses for patients under 45 years of age, as well as smaller community-based studies and case-series specifically examining the incidence of stroke in the young. Trends are discussed along with the relative frequencies of various etiologies. Discussion . Stroke in the young requires a different approach to investigation and management than stroke in the elderly given differences in the relative frequencies of possible underlying causes. It remains the case, however, that atherosclerosis contributes to a large proportion of stroke in young patients, thus, conventional risk factors must be targeted aggressively.